Cognition and classroom quality as predictors of math achievement in the kindergarten year. (February 2016) - Blankson, A. Nayena; Blair, Clancy
Abstract: Using a sample of 171 children, we examined classroom quality as a potential moderator of the link between three distinct but related aspects of cognition (fluid intelligence, crystallized intelligence, and executive functioning) and math achievement across the kindergarten year. Multilevel modeling analyses were conducted to account for nesting of students within classrooms. Results revealed significant aptitude by treatment interactions for fluid and crystallized intelligence, suggesting that classroom practices may affect children differently depending on their abilities. Children with higher levels of fluid intelligence and of crystallized intelligence fared better in higher quality classrooms. Results also provide some support for Cattell's investment hypothesis. Implications of the results are discussed. Highlights: Cognitive abilities are the strongest predictors of early academic achievement. Few studies have examined the link between specific aspects of cognition as predictors of achievement. No studies have examined this question in the context of classroom quality. Relations of fluid and crystallized intelligence with math achievement in kindergarten were moderated by classroom quality.